The Values of Local Wisdom in Preserving Environment in Cireunde Traditional Villages - Logayah, Dina Siti (Universitas Pendidikan Indonesia (UPI), 2021)
Humans are very attached to the natural and cultural environment, this is because humans can cultivate their minds so that they can adapt to their environment. The traditional village of Cireundeu which is located in the southern part of the city of Cimahi shows a place that still maintains the values of local wisdom amid modernity. The purpose of this study is to provide understanding to humans so that they can maintain their environment so that disasters do not occur. This study uses a qualitative approach with naturalistic inquiry methods as the focus, where the researcher does not need to form certain theoretical conceptions or understandings about the field, on the contrary, he can approach his field of attention with a pure mind and allow interpretations to emerge from and be influenced by events. real. The resource persons are traditional leaders, namely Pa Eman and the Cireunde traditional village community in Rukun Tetangga (RT) 02.03 and 05. The results obtained are the values of local wisdom, characteristics, or cultural uniqueness owned by the Cireundeu Traditional Village community, including their relationship with their ecosystem as well as the situation and view that these indigenous communities live side by side with other communities with different levels of welfare and are interesting to study.